Fourth PDIP Congress 2015 : reconciling the President and his Party - Adhi Priamarizki (2015)
The Indonesian Democratic Party of Struggle (PDIP) has begun its national congress until 12 April 2015. This could be a suitable platform for President Joko Widodo (Jokowi) to advance his political position and reconcile with PDIP, while altering Indonesia’s current political configuration.